Pengaruh Temperatur Growth Terhadap Morfologi dan Laju Growth Film Tipis Gallium Antimony yang Ditumbuhkan dengan MOCVD (Jurnal Pilar Sains, 2003)
Undoped galliumantimony apitexiallayers were grown on(100) GaAs substrstes by vertical reactor metal organicchemical vapor deposition. The tridimenthylaminoantimony/trimethylgallium mole fraction (V/III ratio) wasconstant at 2.0 and the growth temperatures were varied 5200C-5400C. The growth pressure in this research wasabout 60 torr. Purified hydrogen was used as gas carrier. By using scanning electron microscope, it was found thatsurface morphology and the growth rate of the layers were strongly depend on growth temperatures. The optimalgrowth temperature in this research was observed at 5400C with more good morphology than the others andhighest growth rate, 1.7 m/h.